Interactions of tree size, competition, and tree species drive carbon accumulation in subtropical mixed forests: A case study of the coniferous-broadleaved mixed forest in Tianmu Mountain - Xiaowen Dou; Mengping Tang (Ecological Indicators, 2025)
Enhancing forests’ carbon storage is crucial in combating climate change. Factors like tree size, species, and competition affect carbon sequestration, but their interactive dynamics and impacts on carbon accumulation are not fully understood. This research utilized 15 years (2006–2021) of fixed plot data from the coniferous-broadleaved mixed forest in the Tianmu Mountain National Nature Reserve, Zhejiang. Various analytical methods including correlation analysis, path analysis, difference analysis, mediation analysis, moderated mediation effect analysis, and hierarchical regression were employed to comprehensively investigate the factors influencing carbon increment in relation to tree size metrics (diameter at breast height (DBH), crown width (CW), and tree height (HT)), competition, and tree species within the forest ecosystem. The results showed that tree carbon increment was positively correlated with tree size parameters (DBH: r = 0.43, CW: r = 0.24, HT: r = 0.32; all P < 0.01) and negatively associated with competition index (r = -0.27, P < 0.01). Path analysis revealed distinct pathways influencing carbon dynamics. CW had the strongest total effect (β = 10.932) through “CW → HT → Carbon increment” and “CW → DBH → Carbon increment” pathways. HT influenced carbon accumulation through DBH mediation. Competition intensity moderated tree size-carbon increment relationships (P < 0.01). Different tree species significantly affected carbon accumulation, with soft broad-leaved species showing the highest increment (median = 29.712 kg). The interaction between DBH and tree species was significant (P < 0.01), indicating species modulation of tree size impact on carbon accumulation. This study elucidates multifactorial mechanisms driving forest carbon sequestration, informing forest stand structure optimization and carbon sink enhancement.